2012
DOI: 10.1182/blood-2012-03-416453
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic kit-on-a-lid: a versatile platform for neutrophil chemotaxis assays

Abstract: Improvements in neutrophil chemotaxis assays have advanced our understanding of the mechanisms of neutrophil recruitment; however, traditional methods limit biologic inquiry in important areas. We report a microfluidic technology that enables neutrophil purification and chemotaxis on-chip within minutes, using nanoliters of whole blood, and only requires a micropipette to operate. The low sample volume requirements and novel lid-based method for initiating the gradient of chemoattractant enabled the measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 41 publications
(30 reference statements)
1
89
0
1
Order By: Relevance
“…For example, we have previously used a similar chemotaxis technology to analyze neutrophils obtained from an arthritic mouse model (53), a disease where neutrophil inflammation is known to regulate dysfunction (54). In this study we observed a ∼10-fold increase in neutrophils from arthritic mice adhering to the substrate, a significant decrease in neutrophil directionality, and no significant difference in chemotaxis velocity compared with wild-type mice (31). Importantly, the neutrophil defect observed in this prior study differs significantly from the asthmatic neutrophil phenotype characterized in this work, suggesting that differences in neutrophil function could be observed to differentiate other inflammatory disorders from asthma.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…For example, we have previously used a similar chemotaxis technology to analyze neutrophils obtained from an arthritic mouse model (53), a disease where neutrophil inflammation is known to regulate dysfunction (54). In this study we observed a ∼10-fold increase in neutrophils from arthritic mice adhering to the substrate, a significant decrease in neutrophil directionality, and no significant difference in chemotaxis velocity compared with wild-type mice (31). Importantly, the neutrophil defect observed in this prior study differs significantly from the asthmatic neutrophil phenotype characterized in this work, suggesting that differences in neutrophil function could be observed to differentiate other inflammatory disorders from asthma.…”
Section: Discussionmentioning
confidence: 56%
“…We adapted a microfluidic neutrophil chemotaxis platform that we previously developed (31) to assay the neutrophil function of mildly asthmatic and nonasthmatic patients in a clinical setting. Briefly, the diagnostic chip has two primary components: (i) a functionalized migration channel in the base, where the rapid neutrophil purification and chemotaxis are performed, and (ii) a multifunction lid that houses all of the reagents required for the diagnostic test and mitigates evaporation, which can be detrimental for long-term open microfluidic experiments (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these devices can configure chemical gradients without the requirement of external fluid delivery instruments (Ge et al 2015;Sackmann et al 2012;Wu et al 2016). Recently, new microfluidic methods have been developed to allow rapid immune cell chemotaxis test directly from a drop of whole blood by incorporating on-chip cell isolation module (Agrawal et al 2008;Hamza and Irimia 2015;Jones et al 2016;Sackmann et al 2012;Sackmann et al 2014b;Wu et al 2016). Several studies have also employed microfluidic cell migration systems for disease orientated applications (Butler et al 2010;Jones et al 2014;Wu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past near two decades, microfluidic devices have become widely used research tools for quantitative cell migration and chemotaxis studies owing to their ability to better control microenvironments, low reagents consumption, simple and automated fluid handling systems (Huang et al 2009;Jeong et al 2010;Jeong et al 2013;Li et al 2016;Sackmann et al 2014a;Vargas et al 2014;Wu et al 2013). Many of these devices can configure chemical gradients without the requirement of external fluid delivery instruments (Ge et al 2015;Sackmann et al 2012;Wu et al 2016). Recently, new microfluidic methods have been developed to allow rapid immune cell chemotaxis test directly from a drop of whole blood by incorporating on-chip cell isolation module (Agrawal et al 2008;Hamza and Irimia 2015;Jones et al 2016;Sackmann et al 2012;Sackmann et al 2014b;Wu et al 2016).…”
Section: Introductionmentioning
confidence: 99%